Voice-Related Symptoms and Their Effects on Quality of Life. (June 2013) - Merrill, Ray M.; Roy, Nelson; Lowe, Jessica
Objectives: The purpose of this study was to identify the extent to which selected voice symptoms formed underlying constructs called factors, and the degree to which these factors influenced specific quality-of-life domains among a group of relatively healthy older adults. Methods: A cross-sectional survey was completed in October 2010 by 461 individuals 50 years of age and older. The questionnaire items included demographics, medical history, health, voice use, and voice symptoms. Quality-of-life indicators were used from the Short Form 36 Health Survey, an 8-scale measure of functional health and well-being. Results: Two clusters of symptoms were identified in the factor analysis. One cluster, consisting of 5 voice-related symptoms and labeled "phonatory effort, " shared all significant negative correlations with health outcomes, whereas the other cluster, consisting of 2 voice-related symptoms and labeled "chronic throat condition, " had a pattern of sharing significant negative correlations with only 3 health outcomes. All voice symptoms had significant negative correlations with general health, bodily pain, and energy/fatigue. Conclusions: Voice-related symptoms share complex relationships with and have negative effects on health outcomes. The specific mechanisms of impact need further research in order for us to better understand these effects on quality of life and how to prevent and treat the symptoms.